Lung function and onset of cardiometabolic diseases in the longitudinal Burden of Obstructive Lung Disease study - Andre F S Amaral; Andrzej Pająk; Thorarinn Gislason; Syed Masud Ahmed; Rain Jogi; Abdul Rashid; Christine Jenkins; Fiona McLean; James Potts; Tobias Welte; Dali Wang; Eric Bateman; et al. (BMJ Open Respiratory Research)
Introduction Previous population-based studies, mainly from high-income countries, have shown that a higher forced vital capacity (FVC) is associated with a lower risk of developing cardiometabolic diseases. The aim of this study was to assess the longitudinal association between spirometry measures and the onset of cardiometabolic diseases across sites in low-income, middle-income and high-income countries.Methods The study population comprised 5916 individuals from 15 countries participating in the Burden of Obstructive Lung Disease baseline and follow-up assessments. Postbronchodilator forced expiratory volume in 1 s (FEV1), FVC and FEV1/FVC were measured at baseline. Participants who reported having doctor-diagnosed hypertension, diabetes, heart disease and stroke at follow-up but not at baseline were considered new cases of these diseases. The association between lung function and the onset of participant-reported cardiometabolic diseases was assessed in each site using regression models, and estimates were combined using random effects meta-analysis. Models were adjusted for sex, age, smoking, body mass index and educational level.Results Participants with greater per cent predicted FVC were less likely to have new-onset diabetes (OR per 10%=0.91, 95% CI 0.84 to 0.99), heart disease (OR per 10%=0.86, 95% CI 0.80 to 0.92) and stroke (OR per 10%=0.81, 95% CI 0.73 to 0.89) during the follow-up period (mean±SD 9.5±3.6 years). A greater percentage of FEV1 was associated with a lower risk of onset of heart disease and stroke. No significant association was found between FEV1/FVC and onset of reported cardiometabolic diseases, except for a higher risk of diabetes (OR per 10%=1.21, 95% CI 1.08 to 1.35) in participants with higher FEV1/FVC.Conclusions The findings of this study suggest that a low FVC is more important than a low FEV1/FVC as a risk factor for developing cardiometabolic diseases. The value of including FVC in risk score models to improve their precision in predicting the onset of cardiometabolic diseases should be explored.